Lactacystin-Induced Model of Hypertension in Rats: Effects of Melatonin and Captopril - Simko, Fedor; Pechanova, Olga; Repova, Kristina; Aziriova, Silvia; Krajcirovicova, Kristina; Celec, Peter; Tothova, Lubomira; Vrankova, Stanislava; Balazova, Lucia; Zorad, Stefan; Adamcova, Michaela (International journal of molecular sciences, 2017)
Lactacystin is a proteasome inhibitor that interferes with several factors involved in heart remodelling. The aim of this study was to investigate whether the chronic administration of lactacystin induces hypertension and heart remodelling and whether these changes can be modified by captopril or melatonin. In addition, the lactacystin-model was compared with NG-nitro-l-arginine-methyl ester (L-NAME)- and continuous light-induced hypertension. Six groups of three-month-old male Wistar rats (11 per group) were treated for six weeks as follows: control (vehicle), L-NAME (40 mg/kg/day), continuous light (24 h/day), lactacystin (5 mg/kg/day) alone, and lactacystin with captopril (100 mg/kg/day), or melatonin (10 mg/kg/day). Lactacystin treatment increased systolic blood pressure (SBP) and induced fibrosis of the left ventricle (LV), as observed in L-NAME-hypertension and continuous light-hypertension. LV weight and the cross-sectional area of the aorta were increased only in L-NAME-induced hypertension. The level of oxidative load was preserved or reduced in all three models of hypertension. Nitric oxide synthase (NOS) activity in the LV and kidney was unchanged in the lactacystin group. Nuclear factor-kappa B (NF-κB) protein expression in the LV was increased in all treated groups in the cytoplasm, however, in neither group in the nucleus. Although melatonin had no effect on SBP, only this indolamine (but not captopril) reduced the concentration of insoluble and total collagen in the LV and stimulated the NO-pathway in the lactacystin group. We conclude that chronic administration of lactacystin represents a novel model of hypertension with collagenous rebuilding of the LV, convenient for testing antihypertensive drugs or agents exerting a cardiovascular benefit beyond blood pressure reduction.
Keywords: Acetylcysteine; Rats; Fibrosis; lactacystin; Light; NG-nitroargininmethylester; Hypertension; hypertension; Captopril; Disease Models, Animal; kaptopril; světlo; mužské pohlaví; Rats, Wistar; srdeční komory; acetylcystein; krysa rodu Rattus; remodelling; antihypertenziva; Antihypertensive Agents; modely nemocí na zvířatech; zvířata; Ventricular Remodeling; Melatonin; melatonin; Heart Ventricles; captopril; hypertenze; fibrosis; fibróza; potkani Wistar; remodelace komor; NG-Nitroarginine Methyl Ester; Male; Animals